Quality Of Health Services With Bpjs Patients Satisfaction In Inpatient Rooms General Hospital University of Muhammadiyah Malang - Winarti; Rusmawati, Aprin; Ellina, Agusta Dian; Widiyanto, Endra (Master of Public Health Program Universitas STRADA Indonesia, 2021)
From the preliminary survey conducted on 10 inpatients using BPJS at the UMM General Hospital, 30-40% stated that they were not satisfied with the quality of service. The purpose of this study was to analyze the relationship between the quality of health services and the satisfaction of BPJS patients in the inpatient room of the UMM Hospital. This research is a quantitative study using a correlation research design. The place of this research is in the inpatient room of UMM Hospital. The study was conducted on October 7 to November 5, 2019. The sample in this study were some inpatients using BPJS aged> 15 years, not anxious, anxious, angry, critical and emergency, totaling 152 patients with Proportionate Random sampling technique. Sampling and analysis used the Pearson statistical test with a significant level (α) of 0.05. The results of the research on the quality of health services of the 5 services studied were the best quality of nutrition services (66.4%), because the nutrition officers provided information about clear diets and timely delivery. Meanwhile, most respondents (55.9%) rated satisfaction as very satisfied. The results showed that there was a relationship between the quality of health services and the satisfaction of BPJS patients in the inpatient room of the UMM Hospital with a significant (Sig) = 0.000 and the strength of the relationship between the test results showed 0.936 which means that the relationship is strong and unidirectional. Based on the research, it is concluded that the higher the value of health service quality, the higher the level of perceived patient satisfaction